Pengelompokan Kabupaten/Kota di Provinsi Jambi Berdasarkan Indikator IPM Menggunakan Metode K-Medoids Cluster - Dinda Aulia Rifani; Cut Multahadah (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2026)
The Human Development Index (HDI) is an index that used to measure the quality of human resources and societal welfare. The HDI value in Jambi Province keeps increasing. Nevertheless, there was a decline in the growth of HLS and RLS in 2024. In addition, the RLS of regencies/cities in Jambi Province just approaching 9 years. Therefore, further analysis of HDI indicators in each regency/city is needed to support the improvement of human development in regencies/cities in Jambi Province. This study aims to group the regencies/cities in Jambi Province based on HDI indicators. The grouping using k-medoids cluster with silhouette coefficient method to determine the optimal number of clusters. The clustering results formed 2 clusters. Cluster 1 consists of 9 regencies/cities with HDI indicators lower than cluster 2, which consists of 2 regencies/cities. Therefore, the results indicate that cluster 2 has better human development quality compared to cluster 1.